The Role of Adat Institution In The Settlement of Criminal Cases Through Restorative Justice In West Sumatera - Yoserwan, Yoserwan; Irzal Rias, A.; Tenofrimer, Tenofrimer; Arma, Diana; Raspati, Lucky (Nagari Law Review, 2023)
The process and mechanism for settling criminal cases always progresses from time to time. One of the mechanisms for settling criminal cases in today's modern era is settlement through Restorative Justice. Although initially, its application was more informal and limited, this concept has developed and has become part of the Criminal Justice System. Settlement mechanisms that involve many related parties and are oriented towards the repair or restoration of various parties affected by a crime are seen as more capable of providing justice. One of the parties involved in the Restorative Justice process besides the perpetrator and the victim is the community. Within the scope of Adat peoples (Masyarakat Adat), community involvement is represented by Adat institutions through Adat leaders. This research examines the role of Lembaga Adat (adat institution). in resolving cases through Restorative Justice in West Sumatra. The research uses empirical legal research methods, namely by collecting data either through law enforcement agencies or customary institutions. The results of the research were analyzed by juridical qualitative. The results of the research show that in West Sumatra the settlement of criminal cases through restorative justice has involved Adata institutions represented by Adat leaders. Community involvement is formed through a memorandum of understanding between law enforcement agencies, in this case, the police and prosecutors institution, and involves Adat institutions in the implementation process. In the future, the involvement of Adata institutions in the settlement of criminal cases, especially through restorative justice, needs to be optimized, because the justice obtained will be more in line with the feelings of justice in society.